2008
DOI: 10.1021/jf800617g
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Properties of Thymus vulgaris Leaves: Comparison of Different Extracts and Essential Oil Chemotypes

Abstract: Thyme (Thymus vulgaris L., Lamiaceae) is a subshrub from the Lamiaceae family with plants that are rich in essential oils and antioxidative phenolic substances. Twelve accessions originating from southern France and the variety 'Deutscher Winter' were grown in an experimental field in eastern Austria. Leaf samples from these plants as well as from a commercial thyme rich in thymol were analyzed for their essential oil and the antioxidative potential in various extracts. The assays for antioxidative activity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
96
3
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(127 citation statements)
references
References 25 publications
10
96
3
6
Order By: Relevance
“…Although the IC 50 value of the T. vulgaris essential oil was greater than that of -tocopherol (the positive control), the T. vulgaris essential oil might prove an effective antioxidant in many applications. The antioxidant activities of the T. vulgaris essential oil were similar to those determined in previous studies, 28,29) but the antioxidant activities of the L. anagallis and P. fragrans essential oils are described for the first time here.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Although the IC 50 value of the T. vulgaris essential oil was greater than that of -tocopherol (the positive control), the T. vulgaris essential oil might prove an effective antioxidant in many applications. The antioxidant activities of the T. vulgaris essential oil were similar to those determined in previous studies, 28,29) but the antioxidant activities of the L. anagallis and P. fragrans essential oils are described for the first time here.…”
Section: Resultssupporting
confidence: 86%
“…This correlates with the antioxidant activities of the T. vulgaris essential oil, because essential oils with elevated proportions of thymol and carvacrol exhibit upregulated antioxidant activities. 28) Also, previous research has indicated that carvacrol in thyme oils suppresses the LPS-induced expression of cyclooxygenase-2 (COX-2) mRNA and protein, which can cause repression of inflammation. 34) Thus, the T. vulgaris essential oil (which consists of 2.03% carvacrol) exhibited a significant anti-inflammatory activity in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in a study where different extracts and essential oil chemotypes of Thymus vulgaris were screened, the highest activity was shown by the oils that were abundant in thymol (22).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding Rosmarinus officinalis EOs (Lamiaceae family), it has been previously reported variations in the chemical composition and biological activity of plants growing in different countries [8,20]. This oil was rich in phenolic acids such as rosmarinic acid and carnosic acid with strong antioxidant properties, it has been proposed to be used as preservation for certain foods and nutraceutical products to avoid synthetic antioxidants [21]. However, data regarding this activity of essential oils of thyme and rosemary are not abundant and the methods for determination are different [22,23].…”
Section: Introductionmentioning
confidence: 99%